Production of ZA-27 Alloy by New Rheocasting Process - Abood, Adnan Naama; Habeb, Tahar Salah (Sulaimani Journal for Pure and Applied Sciences, 2008)
The present work encompasses the grains refining of microstructure of Zn-Al alloy (ASTM B669 ZA-27) ingots without addition of refining agents or using stirring, that is, by using the New Rheocasting (NRC). AISI 316 stainless steel mould is employed with inclination angle of 75o and 1.2 V/A ratio. The pouring temperatures are 532 oC, 522 oC, and 502 oC, while the quenching occurs at different temperatures. The examination shows that all NRC ingots have microstructure of refined equaxial grains in the range of 27- 36 μm, while the percentage of volume fraction of α-Al phase was varied from 0.56 to 0.76. The value of circularity was in the range of 1.33-1.65. The NRC ingots achieved less coarsening kinetic than critical value which shows that there is a limited increase in the grain size and coalescence of reheating. Tensile strength, Yield strength, and Elongation of ZA-27 alloy which was made by NRC process, increased to 18%, 11%, and 32% respectively compare to Gravity Die Casting (GDC) ingots due to formation of equaxil grains along all the cross section in addition to smaller grains size.
Keywords: New Rheocasting; ZnAl alloy; Pouring Temperature; QuenchingTemperature; Equaxial Grain; Mechanical Properties